Biosorption of heavy metals by Talaromyces helicus: a trained fungus for copper and biphenyl detoxification - Romero, María Cristina (2006)
At present, it is common to observe environments with organic and inorganic pollution, defined as co-contamination. Most industrial and urban effluents releases both pollutant types, leading to a complex environmental problem, as the biota must be tolerant to both xenobiotics. T. helicus, an efficient strain to degrade biphenyl, was trained with high copper levels, and became co tolerant to cobalt, lead and cadmium when was cultured in their presence. The copper adaptation was the result of physiological mechanisms, and the activated biochemical processes conferred resistance to Cu2+ as well as to other heavy metals. Furthermore, the Cu2+ adaptation of the mycelium was also transferred to the spores, that removed twice as much copper from solution than those of the no trained parentals. Interestingly, metals combinations were less toxic than single ones, and co tolerance development indicated that the cellular mechanisms that conferred resistance were non-specific, so the micobiota isolated from co contaminated environments often exhibited resistance to more than one ions. These results emphasized the detoxification abilities of T. helicus and the adaptation to heavy metals and biarylic compounds. This data is significant for the environmental biotechnology, suggesting that such tolerance and co tolerance could be acquired in natural environments. So a simple bioremediation strategy could enhance the detoxification of these polluted areas, as the degrader organisms could be present.